2017
DOI: 10.1093/ptj/pzx039
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Validity, and Minimal Detectable Change of Four-Step Stair Climb Power Test in Community-Dwelling Older Adults

Abstract: The 4SCPT shows scientific promise as a valid and reliable leg power measurement among community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Similarly, the knee extensor muscles play a dominant role in the progression from one step to the next in stair climbing, together with the ankle plantar flexors [34, 35]. The importance of knee-extensor strength and power in SA and STS have already been established in previous research [31, 3639]. It is therefore not surprising that, in the current study, both SA and STS performance were related to multi-joint LEP.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Similarly, the knee extensor muscles play a dominant role in the progression from one step to the next in stair climbing, together with the ankle plantar flexors [34, 35]. The importance of knee-extensor strength and power in SA and STS have already been established in previous research [31, 3639]. It is therefore not surprising that, in the current study, both SA and STS performance were related to multi-joint LEP.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, sensor-based power parameters (r = 0.80–0.81) were clearly more associated with LEP than duration parameters (r = -0.41 –-0.66) in both SA and STS tests, which stresses the added value of power parameters in functional tests. It should be noted that previous research has used other simple alternative ways to estimate power in SA and STS tests, for example with smartphone applications [40, 41], Tendo Weightlifting Analyzer [42], or by only using a stopwatch [31, 32]. Because stopwatch-based approaches have the highest potential for large-scale implementation, we additionally calculated power during SA and STS based on performance durations instead of accelerometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCT appears to have greater responsiveness to detect change (expected improvement) than patient-report questionnaires during the acute stages after knee replacement surgery and was shown to be the most responsive physical performance measure in the early recovery period. 34 Ni et al, 35 showed excellent reliability (r = 0.95) and strong validity of the four-step test, providing evidence for its potential utility as a clinical measure of lower limb power among community-dwelling older adults. 34 30-sec chair stand test.…”
Section: Outcome Measuresmentioning
confidence: 95%
“…In this regard, there is great interest in identifying clinical physical performance measures able to characterise the functional impairment of older adults, particularly for balance, gait, and stair climbing. Regarding the latter, the Stair Climb Power Test, 1-minute Stair Climb Test, 4-Step Stair Climb Power Test and 12-Step Stair Test have been developed for clinical evaluation [2][3][4]. Indeed, since climbing stairs involves a full control of balance and gait, as well as a sufficient muscular strength, assessing functional parameters while climbing stairs is clinically important for an overall description of how healthy the ageing process is.…”
Section: Introductionmentioning
confidence: 99%